2020
DOI: 10.22377/ajp.v14i03.3683
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction: A medication incident is any avertable event that may lead or cause to improper medication use or patient harm while the medication is in the control of the health-care professional, consumer, or patient. Professional practice, procedure, drug products, and systems may be related to medicated incidents. Objective: The main purpose of this study is to investigate these incidents such as types of prescribing errors, evaluate the occurrence of drug-drug interactions, and assess the rationality of e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Forty-seven percent of respondents did not know that non-prescription medications can cause renal failure. Before utilizing non-prescription medications, 40% of participants said they visit a doctor or pharmacist, in contrast, a different study on the incidence of self-medication in Saudi Arabia's urban individuals that visited community pharmacies found that 69% of those surveyed stated they kept their remaining medications on standby for later usage (Khan et al, 2020).…”
Section: Diabetes Mellitusmentioning
confidence: 93%
“…Forty-seven percent of respondents did not know that non-prescription medications can cause renal failure. Before utilizing non-prescription medications, 40% of participants said they visit a doctor or pharmacist, in contrast, a different study on the incidence of self-medication in Saudi Arabia's urban individuals that visited community pharmacies found that 69% of those surveyed stated they kept their remaining medications on standby for later usage (Khan et al, 2020).…”
Section: Diabetes Mellitusmentioning
confidence: 93%